2016
DOI: 10.1111/jdi.12593
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of lipid‐lowering action of the dipeptidyl peptidase‐4 inhibitor, anagliptin, in low‐density lipoprotein receptor‐deficient mice

Abstract: Aims/IntroductionDipeptidyl peptidase‐4 inhibitors are used for treatment of patients with type 2 diabetes. In addition to glycemic control, these agents showed beneficial effects on lipid metabolism in clinical trials. However, the mechanism underlying the lipid‐lowering effect of dipeptidyl peptidase‐4 inhibitors remains unclear. Here, we investigated the lipid‐lowering efficacy of anagliptin in a hyperlipidemic animal model, and examined the mechanism of action.Materials and MethodsMale low‐density lipoprot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
31
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(36 citation statements)
references
References 30 publications
5
31
0
Order By: Relevance
“…The present study showed that in type 2 diabetes mellitus patients treated with ANA, the %change in LDL-C level at 24 weeks correlated significantly with the %change in apoB-100 levels (Spearman, P = 0.028, r = 0.424), but not with that in apoB-48 levels (Spearman, P = 0.951, r = -0.013). This finding suggests that the mechanism of action of ANA involves the suppression of cholesterol synthesis in the liver, similar to the possible mechanism reported by Yano et al 17 .…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…The present study showed that in type 2 diabetes mellitus patients treated with ANA, the %change in LDL-C level at 24 weeks correlated significantly with the %change in apoB-100 levels (Spearman, P = 0.028, r = 0.424), but not with that in apoB-48 levels (Spearman, P = 0.951, r = -0.013). This finding suggests that the mechanism of action of ANA involves the suppression of cholesterol synthesis in the liver, similar to the possible mechanism reported by Yano et al 17 .…”
Section: Discussionsupporting
confidence: 90%
“…Yano et al . showed that in LDL‐C receptor‐deficient mice, ANA did not affect sterol regulatory element‐binding protein 1c (SREBP1c), a transcription factor involved in TG synthesis in the liver, but reduced sterol regulatory element‐binding protein 2, a transcription factor involved in cholesterol synthesis in the liver.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…First of all, we confirmed the lipid‐lowering effect of anagliptin in the mice, just as in a previous clinical study, with anagliptin treatment reducing the serum total cholesterol and non‐HDL‐C concentrations. Similar effects of anagliptin have been shown in ApoE‐deficient mice, LDL receptor knockout mice and cholesterol‐fed rabbits. Yano et al .…”
Section: Discussionsupporting
confidence: 55%
“…Anagliptin treatment significantly decreased the plasma total cholesterol (14% reduction, p<0.01) and triglyceride levels (27% reduction, p<0.01). The results indicated that the DPP4 inhibitor, anagliptin, exhibited a lipid-lowering effect in a hyperlipidemic animal model, and suggested that the down regulation of hepatic lipid synthesis was involved in the effect [31].…”
Section: Dpp4 Inhibitors In the Management Of Hyperlipidemiamentioning
confidence: 88%